2022
DOI: 10.1002/aoc.6765
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)–PPh3 complexes of halogen substituted acylthiourea ligands: Biomolecular interactions and in vitro anti‐proliferative activity

Abstract: Herein, we report the synthesis of four new Pd(II) acylthiourea complexes (C1–C4) to study the effect of halogen substituted acylthiourea ligands on the biological applications of their Pd(II)–PPh3 complexes. The complexes were characterized by various spectroscopic and analytical methods. The distorted square planar geometry of complexes was confirmed by single crystal X‐ray diffraction study, which also revealed the bidentate (N, S) coordination of the ligands with Pd(II). Interactions of the complexes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…In the spectra of complexes, a noticeable shift (from 1248–1269 to 1171–1186 cm –1 ) in the stretching frequency of CS was seen, whereas almost no change in the CO stretching frequency was observed, indicating the coordination of S to the Ru­(II) ion. The stretching frequencies observed at 710–721, 1076–1092, and 1437–1452 cm –1 confirmed the presence of PPh 3 in the complexes . FT-IR spectra of the complexes are depicted in Figure S1.…”
Section: Resultsmentioning
confidence: 59%
“…In the spectra of complexes, a noticeable shift (from 1248–1269 to 1171–1186 cm –1 ) in the stretching frequency of CS was seen, whereas almost no change in the CO stretching frequency was observed, indicating the coordination of S to the Ru­(II) ion. The stretching frequencies observed at 710–721, 1076–1092, and 1437–1452 cm –1 confirmed the presence of PPh 3 in the complexes . FT-IR spectra of the complexes are depicted in Figure S1.…”
Section: Resultsmentioning
confidence: 59%
“…The slope to intercept ratio was used to calculate the intrinsic binding constant K b and the plots are found in Figure 2b. The inclusion of aromatic pyridine and pyrazole moieties boosted the π–π stacking interactions, resulting in greater planarity, which allowed the complexes to glide more freely between DNA base pairs, which is why all four complexes showed good K b values 31 …”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of aromatic pyridine and pyrazole moieties boosted the π-π stacking interactions, resulting in greater planarity, which allowed the complexes to glide more freely between DNA base pairs, which is why all four complexes showed good K b values. 31 The corresponding copper complex's ability to bind to DNA could not be directly predicted by emission spectrum analyses as they were non-fluorescent at room temperature in solution or in the presence of CT DNA. Due to this, a fluorometric competitive binding experiment was carried out utilizing the potent intercalator ethidium bromide (EB) to study in detail the interaction pattern of DNA and metal complex.…”
Section: Binding With Ct Dnamentioning
confidence: 99%
“…20). 87 Anticancer activity of the synthesized Cu(I) complexes (79ae) of acyl thiourea was evaluated against breast cancer cells MCF7, T47D, and MDA MB 231 by Dorairaj et al Complexes showed dose-dependent activity with the best results observed as, IC 50 0.75-0.98 ± 0.01 mM against MCF7 cancer cells, 0.75-0.94 ± 0.02 mM against T47D cancer cells and 0.68-0.95 ± 0.02 mM against MDA MB 231 cancer cells, when exposed to different concentration of complexes for 72 h. These results were better compared to the standard drug Cisplatin. Amongst the complexes (79d) showed the highest activity due to strong interaction with biomolecules, similarly complexes (79b-e) showed high activity as compared to (79a) because of its lipophilic nature which allowed its penetration across the membrane of cells, and the second reason was the presence of substituent on aromatic moiety attached to thioamide N (Fig.…”
Section: Biological Aspectsmentioning
confidence: 99%